2022
DOI: 10.5483/bmbrep.2022.55.4.126
|View full text |Cite
|
Sign up to set email alerts
|

Reactive microglia and mitochondrial unfolded protein response following ventriculomegaly and behavior defects in kaolin-induced hydrocephalus

Abstract: Ventriculomegaly induced by the abnormal accumulation of cerebrospinal fluid (CSF) leads to hydrocephalus, which is accompanied by neuroinflammation and mitochondrial oxidative stress. The mitochondrial stress activates mitochondrial unfolded protein response (UPRmt), which is essential for mitochondrial protein homeostasis. However, the association of inflammatory response and UPRmt in the pathogenesis of hydrocephalus is still unclear. To assess their relevance in the pathogenesis of hydrocephalus, we establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Microglia activation has been associated with both vasospasm and hydrocephalus and is closely regulated by the IL-6 pathway and NLRP3 in ammasome. [31] We had previously reported bene t of NLRP3 inhibition following SAH. In this paper, we found that IL-6 blockade had signi cant regulation on another armn of the in ammatory spectrum starting on post SAH day 3 and extending to day 5.…”
Section: Discussionmentioning
confidence: 97%
“…Microglia activation has been associated with both vasospasm and hydrocephalus and is closely regulated by the IL-6 pathway and NLRP3 in ammasome. [31] We had previously reported bene t of NLRP3 inhibition following SAH. In this paper, we found that IL-6 blockade had signi cant regulation on another armn of the in ammatory spectrum starting on post SAH day 3 and extending to day 5.…”
Section: Discussionmentioning
confidence: 97%
“…To accomplish their functions, microglia consume substantial amounts of energy, a heightened demand that is met by an increase in the bioenergetic metabolism of mitochondria [ 22 ]. We previously reported that activated microglia and the UPRmt (reflecting mitochondrial stress) are involved in the pathogenic mechanism underlying hydrocephalus in a kaolin-induced hydrocephalus mouse model [ 16 ]. To further establish the relationship between activated microglia and the UPRmt, we analyzed the microglia-mediated inflammatory response, UPRmt and mitochondrial OXPHOS function in LPS-stimulated BV-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…LPS also activates the UPRmt in cardiomyocytes, which act to reduce inflammation-mediated myocardial injury [ 15 ]. We previously reported that microglia are activated and the UPRmt is upregulated in a mouse model of kaolin-induced hydrocephalus [ 16 ]. However, the potential link between microglia-induced neuroinflammation and the UPRmt has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial stress has been employed as a strategy to mitigate excessive damage resulting from neuroinflammation. A study by Zhu et al demonstrated the activation of microglia and the UPR mt (reflecting mitochondrial stress) are involved in the pathogenic mechanism underlying hydrocephalus in a kaolin-induced hydrocephalus mouse model in C57BL/6J mice [ 96 ]. Subsequent research by the same group suggested a link between pro-inflammatory microglial polarization and UPR mt [ 97 ].…”
Section: Cross-talk Between Mitochondrial Stress and Neuroinflammatio...mentioning
confidence: 99%